2023
DOI: 10.3390/jof9030382
|View full text |Cite
|
Sign up to set email alerts
|

A Feasibility Study on the Recall of Metallophilic Fungi from Fe(III)-Contaminated Soil and Evaluating Their Mycoremediation Capacity: Experimental and Theoretical Study

Abstract: Mycoremediation is one of the most attractive, eco-friendly, and sustainable methods to mitigate the toxic effects of heavy metals. This study aimed to determine the mycoremediation capacity of metallophilic fungi isolated from heavy-metal-contaminated soil containing a high Fe(III) concentration (118.40 mg/kg). Four common fungal strains were isolated, including Curvularia lunata, Fusarium equiseti, Penicillium pinophilum, and Trichoderma harzianum. These fungal strains were exposed to gradually increasing co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Bioremediation can be applied using microorganisms such as algae, bacteria, and fungi [ 17 ]. Studies showed that bioremediation by fungi is a practical, appropriate, and eco-friendly procedure [ 18 , 19 ]. Ascomycetes are typical fungi that are essential in bioremediation as they are fast-growing and low in cost [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Bioremediation can be applied using microorganisms such as algae, bacteria, and fungi [ 17 ]. Studies showed that bioremediation by fungi is a practical, appropriate, and eco-friendly procedure [ 18 , 19 ]. Ascomycetes are typical fungi that are essential in bioremediation as they are fast-growing and low in cost [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Bioremediation, on the other hand, utilizes microorganisms to degrade organic pollutants, making it suitable for certain types of wastewaters. 8,10 Activated sludge mechanisms involve the use of biological processes for the treatment of a Applied Mineralogy and Water Research Lab (AMWRL), Geology Department, Faculty of Science, Beni-Suef University, Beni Suef, 62521, Egypt. E-mail: ahmed.zayed@ science.bsu.edu.eg; mostafa_masoud@science.bsu.edu.eg wastewater, and it is particularly effective in removing organic matter.…”
Section: Introductionmentioning
confidence: 99%
“…15 Conversely, the adsorption process is the most recommended treatment strategy due to its high efficiency, applicability in a wide pH range, low cost, simplicity, and viability for large-scale applications. 10,11,16 To carry out adsorption studies and to determine the essential parameters for controlling the removal of contaminants from wastewater, both batch and column methods are necessary. 17 Fixed bed adsorption column represents one of the most popular and effective methods for removing contaminants from water.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations